Sex determination from the pulp tissue of deciduous teeth exposed to natural soil and wet clay - A PCR study - Prachi Suman; R Manju; Veena A Shetty; Amitha M Hegde; Muthtamil; Shama Rao (Wolters Kluwer Medknow Publications, 2020)
Context: Dental tissue remains are the toughest, and chemically, the most stable tissue in the body. Its high resilience in the events of fire and bacterial decomposition makes them vital for DNA analysis by PCR method. Aims: Determination of sex of children through molecular analysis of pulp tissue of exfoliated deciduous teeth stored in different media and analyzed after a different time period. Settings and Design: Sixty samples of deciduous teeth were divided into three groups. Group IA and Group IIA were stored in natural soil and wet clay for 1 month, respectively. Group IB and Group IIB were stored in natural soil and wet clay for 6 months, respectively. Group III was analyzed immediately after extraction. Methods and Material: Sex determination was carried out in five steps: Pulp tissue removal, DNA isolation, DNA quantification, PCR amplification, Sex determination. X and Y specific chromosomes from each sample were amplified and compared. Statistical Analysis Used: Kruskal-Wallis test, Dunn's test, and Wilcoxon signed rank test. Results: Group III revealed the highest amount of DNA quantified. Amount of DNA quantified after 6 months of storage in natural soil and wet clay decreased in both the groups with the samples stored in wet clay showing a maximum decrease. Results of the PCR analysis also showed 100% accuracy rate in the samples of Group III. Conclusions: Sex determination from pulp tissue depends a lot on the quality and quantity of DNA extracted. Sex could be effectively determined among the samples evaluated immediately after extraction. This ability decreases as the storage condition changes and the time period increases. Samples stored in wet clay were found to show the least sex identification ability than dry soil.